Effects of Environmental Factors on the Performance of Anfo Tests in Turkey - Gulsev Uyar Aldas; M. Oguz Ozkazanc (International Society of Explosives Engineers, 2001)
Because of its safety, being easy to handle, relatively inexpensive and containing a lot of energy, ANFO is the most popular and widely used explosive in Turkey as well as other countries in the world. According to change dated May 14th 1999 on the regulation 87/12028 related with explosives, blasters are not allowed to mix ammonium nitrate and fuel oil in the tield to make ANFO. Instead of this, they have been forced to use the ready ANFO prepared by explosive producer firms. As a result of this obligation, the use of technical nitrate for agricultural purpose and mixing AN and fuel oil in unsuitable conditions have been prevented. Indeed, wrong mixture means waste of energy and money.